Role of Permeability in the Activities of β-Lactams against Gram-Negative Bacteria Which Produce a Group 3 β-Lactamase - Matsumura, Naoki (American Society for Microbiology, 1999)
The production of a group 3 β-lactamase permitted Escherichia coli to raise the MICs of ceftazidime, cefpirome, and meropenem greatly but those of imipenem and piperacillin only slightly. The ratios of maximum rate of hydrolysis to K(m) of ceftazidime, cefpirome, and piperacillin were lower than those of meropenem and imipenem for the group 3 β-lactamase. The permeability coefficients for piperacillin and meropenem were higher than those for ceftazidime and cefpirome. Imipenem had the highest permeability coefficient.